Factors Affecting in Planning of Current Expenditurs For Federal Public Budget of State: An Applied Research For ASample of Health Ministry Depatments (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Increasing interest in planning at the level of government units as a means to manage the physical and human resources, direct and invest in areas that would include an increase in the economies of the general government units that are part of the general economics of the state.The research problem lies in the introduction of the factors influencing the ongoing expenses that adversely affect the financial planning process at the level of the Ministry of Health Planning, which affects the quality of services provided to citizens, so I sought the researchers to study the reality of financial planning in some of the Ministry of Health and health departments through the analysis of current budgets and diagnose deviations in the implementation of those budgets, I suggest a model for the planning of current expenditure.The most hypothesis Search ((Failure to follow specific scientific steps going through the financial planning process will lead to a lack of linkage between the influencing factors and the stage of the ongoing budget expenditures Planning.One of the main conclusions reached by the study is the large number of violations of certain laws and regulations specific to the process of exchange which negatively affect the estimate of current expenditures properly, are the basis of the result of the large number of laws governing the work of the Ministry of Health and instructions, and the most important recommendations is the need to study the actual needs of the units of public spending and by The proposed specimen for Tvlal current budget to total general budget and the advancement of the investment side